NEUROCHEMICAL ALTERATIONS ASSOCIATED WITH BORDERLINE PERSONALITY DISORDER - Atmaca, Murad; Karakoc, Tevfik; Mermi, Osman; Gurok, M. Gurkan; Yildirim, Hanefi (Sage Publications Inc, 2015)
In neuroimaging on borderline personality disorder, prior studies focused on the hippocampus and amygdala, as mentioned above. However, no study investigated whether there were neurochemical changes in the patients with borderline personality disorder. Therefore, in the present study, we aimed to investigate neurochemical change of patients diagnosed with borderline disorder and hypothesized that neurochemicals would change in the hippocampus region of these patients. Seventeen patients and the same number of healthy control subjects were analyzed by using a 1.5 Tesla GE Signa Imaging System. N-acetylaspartate (NAA), choline compounds (CHO), and creatine (CRE) values of hippocampal region were measured. The mean NAA/CRE ratio in the hippocampus region was significantly reduced in the patients with borderline personality disorder compared to that of healthy control subjects. In addition, NAA/CHO ratio of the patients with borderline personality disorder was also significantly reduced when compared to that of healthy subjects. There was no difference in the ratio of CHO/CRE. In summary, we present evidence for reduced NAA in the patients with borderline personality disorder.
Keywords: borderline personality disorder; N-acetylaspartate; creatine; MRS